Time to focus on outcome assessment tools for childhood vasculitis - Karaoglu Abdulbaki; Ayaz Nuray; Luqmani Raashid; Demirkaya Erkan; Ozen Seza (BMC, 2011)
Abstract Childhood systemic vasculitides are a group of rare diseases with multi-organ involvement and potentially devastating consequences. After establishment of new classification criteria (Ankara consensus conference in 2008), it is now time to establish measures for proper definition of activity and damage in childhood primary vasculitis. By comparison to adult vasculitis, there is no consensus for indices of activity and damage assessment in childhood vasculitis. Assessment of disease activity is likely to become a major area of interest in pediatric rheumatology in the near future. After defining the classification criteria for primary systemic childhood vasculitis, the next step was to perform a validation study using the original Birmingham vasculitis activity score as well as the disease extent index to measure disease activity in childhood vasculitis. Presently, there are efforts in place to develop a pediatric vasculitis activity score. This paper reviews the current understanding about the assessment tools (i.e., clinical features, laboratory tests, radiologic assessments, etc.) widely used for evaluation of the disease activity and damage status of the children with vasculitis.